2000
DOI: 10.1006/jfbi.1999.1161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish size on spawning time in Norwegian spring-spawning herring

Abstract: During October-January in a northern Norwegian fjord system and in February-March at the main western Norway spawning grounds, an index I G of gonad weight of spring-spawning herring Clupea harengus in percentage of expected gonad weight at full maturity for a given total length L T , tended to increase with L T in the range 27-31 cm as the proportion of recruit spawners decreased. Insignificant differences in I G were found between L T groups in the range 32-37 cm (repeat spawners). This is contrary to that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The positive effect of L T on oocyte diameter in December indicates an earlier onset of spawning in large female A. marinus . A similar length effect on relative ovary size has been linked to two waves of spawning in Norwegian spring spawning C. harengus (Slotte et al, ). Although little is known about the precise timing of spawning in A. marinus , the present study suggests that asynchrony in the onset of spawning could extend the period over which individuals spawn within a population.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The positive effect of L T on oocyte diameter in December indicates an earlier onset of spawning in large female A. marinus . A similar length effect on relative ovary size has been linked to two waves of spawning in Norwegian spring spawning C. harengus (Slotte et al, ). Although little is known about the precise timing of spawning in A. marinus , the present study suggests that asynchrony in the onset of spawning could extend the period over which individuals spawn within a population.…”
mentioning
confidence: 59%
“…The length effect on oocyte development probably reflects differences in energy stores as larger A. marinus attain a higher condition by the onset of over‐wintering (Rindorf et al, ). The early onset of spawning has also been found to be related to somatic condition in C. harengus , another capital breeder (Slotte et al, ). Indeed, some of the most extensive evidence of size‐dependent spawning time has been found in C. harengus (Ware & Tanasichuk, ) and it is thought that this trend in wild fish is caused by fish of different sizes experiencing different environmental conditions, such as temperature.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…One hypothesis is that larger Greenland halibut females start maturing earlier in the year compared to smaller females. This is for instance seen in herring Clupea harengus L. and several other fish species (Slotte et al ., 2000). A study on Greenland halibut in the Barents Sea showed that the large fast growing individuals started the spawning migration earlier than smaller ones (Albert, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This migration has been suggested to be size‐dependent with larger fishes flooding into the spawning grounds first and spawning earlier compared to smaller specimens (Dragesund et al ., 1980; Hay, 1985; Dawson, 1986; Lambert & Messieh, 1989). Moreover, to be age‐dependent with younger fishes spawning first ( C. harengus ; Lambert, 1987), and finally in some cases repeat spawners have been found to spawn first and recruit spawners later (Slotte et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%